The Emerging Role of Transnasal Humidified Rapid-Insufflation Ventilatory Exchange (THRIVE) Technique and C-MAC Videolaryngoscope for Difficult Airway Management in a Patient with Klippel–Feil Syndrome: A Case Report - Anjana Kashyap; Alia Vidyadhara; Vidyadhara Srinivasa; Madhava P. Kanhangad (Journal of Neuroanaesthesiology and Critical Care)
Klippel–Feil syndrome (KFS) is a rare autosomal dominant congenital anomaly characterized by failure in fusion of the cervical vertebrae. There have been no case reports describing the use of a combination of transnasal humidified rapid-insufflation ventilatory exchange (THRIVE) and C-MAC videolaryngoscope in the airway management of an adult patient with KFS. Our patient was a 50-year-old male diagnosed with KFS posted for revision robotic-assisted cervical C2-C4 laminectomy and fusion. He was successfully intubated with the help of THRIVE and C-MAC videolaryngoscope. During induction and intubation, saturation remained above 96%. At the end of surgery, patient was extubated after satisfying all difficult airway extubation criteria. THRIVE and C-MAC videolaryngoscope have been promoted for use in anticipated difficult airway scenarios. We report the first successful usage of THRIVE and C-MAC videolaryngoscope to secure the airway in a patient with KFS.